Factors impacting trauma-specific quality of life following injury: A multi-center assessment in Lebanon. Issue 10 (October 2022) - Elreichouni, Ali; Al-Hajj, Samar; Maciejewski, Kaitlin R; Ariss, Abdel Badih; Mowafi, Hani
Highlights: Individuals experienced reduced levels of employment and significant reductions in income as a result of injury. Roughly 65% of out-of-pockets costs associated with injury were borrowed. One-fourth of patients could not afford necessary follow-up care. Patients from the American University of Beirut, who were on average more educated and wealthy, were less financially impacted and had better TQOL outcomes than patients at the Rafic Hariri Governmental Hospital and Geitawi Hospital. Abstract: Objective: : Injuries account for a large portion of the global burden of disease, representing over 10% of all disability adjusted life years (DALYs). This study analyzes the economic impact of injury for those experiencing moderate-to-severe injury in Beirut, Lebanon. It further examines the impact of different demographic and socioeconomic factors on trauma-specific quality of life 1–2 years following injury. Methods: : This was a prospective cohort study following patients 1–2 years after being treated for injury at one of three hospitals in Beirut, Lebanon. Patients interviewed by phone. In addition to questions on financial impact, access to healthcare, and socioeconomic status, the Trauma-specific Quality of Life (TQoL) Questionnaire was used to assess quality of life following injury. Multivariable linear models were constructed to examine TQoL and demographics among institutes. Results: : 116 patients completed interviews. The average out-of-pocket cost of injury was 2975.42 USD, 65% of which was borrowed. 21% of people lost employment due to injury. Patients at Geitawi Hospital and the Rafic Hariri Governmental Hospital borrowed more on average and had higher reductions in employment than patients at the American University of Beirut Medical Center (AUBMC). There was a loss of income for those employed at the time of injury, with a mean monthly loss of 261.6 USD. The economic impact of injury was 10, 329.00 USD. 25% of patients reported difficulty with accessing follow-up care, predominantly due to cost. Mean-adjusted Trauma-specific Quality of life (TQoL) was highest at AUBMC. Education was associated with functional recovery in the TQoL questionnaire; for every additional year of education there was an increase in the functional recovery domain of 0.03. Conclusion: : Individuals that experienced moderate-to-severe injury in Beirut, Lebanon, suffered financial repercussions, including reductions in income, less employment, or unemployment. Across all patients surveyed, higher level of education was associated with better functional quality of life. More study into the intricacies of accessing healthcare care in Lebanon, especially given the current economic and political climate, are crucial to maintain the health of those experiencing injury and can help inform targeted interventions.